Plan de mejoramiento en habilitación de servicios para la clínica del trabajador, según resolución 3100 de 2019 (2022)
The unique habilitation systems governed by Resolution 3100 of 2019 in accordance with the stipulations of Decree 1011 of 2006, which establishes the unique habilitation system (SUH) and the minimum quality conditions for health care in public and private institutions in Colombia, is the initial step to reach the Quality Accreditation systems. The purpose of this research was to carry out an improvement plan that helps in the fulfillment of the criteria established in Resolution 3100 of 2019 and applied to the Clínica del Trabajador S.A.S located in the city of Bogotá.